(untitled) (Herald of the National Children’s Medical Center, 2024)
Pediatric surgery is characterized by the rapid development and introduction of endosurgical methods of diagnosis and treatment into the practice of the surgeon. The endoscopic technique is the most common of all minimally invasive interventions. With the improvement of surgical techniques, the possibilities of using minimally invasive techniques in the treatment of abdominal pathology in children of different age groups are opening up.